175k views
2 votes
What is the inverse of the function f(x) = 2x + 1?

User Martonx
by
5.3k points

2 Answers

5 votes

Answer:


f^(-1)(x) =
(x-1)/(2)

Explanation:

let y = f(x) and rearrange making x the subject, that is

y = 2x + 1 ( subtract 1 from both sides )

y - 1 = 2x ( divide both sides by 2 )


(y-1)/(2) = x

Change y back into terms of x


f^(-1)(x) =
(x-1)/(2)

User Johannes Charra
by
5.1k points
6 votes

Answer:

1 + 2x = f(x) i believe

Explanation:

User Chrisarton
by
5.4k points